Changing Perspectives on the Role of DnaA-ATP in Orisome Function and Timing Regulation - Leonard, Alan C.; Rao, Prassanna; Kadam, Rohit P.; Grimwade, Julia E. (Frontiers in Microbiology, 2019)
Bacteria, like all cells, must precisely duplicate their genomes before they divide. Regulation of this critical process focuses on forming a pre-replicative nucleoprotein complex, termed the orisome. Orisomes perform two essential mechanical tasks that configure the unique chromosomal replication origin, oriC to start a new round of chromosome replication: 1) unwinding origin DNA and 2) assisting with loading of the replicative DNA helicase on exposed single strands. In Escherichia coli, a necessary orisome component is the ATP-bound form of the bacterial initiator protein, DnaA. DnaA-ATP differs from DnaA-ADP in its ability to oligomerize into helical filaments, and in its ability to access a subset of low affinity recognition sites in the E. coli replication origin. The helical filaments have been proposed to play a role in both of the key mechanical tasks, but recent studies raise new questions about whether they are mandatory for orisome activity . It was recently shown that a version of E. coli oriC (oriCallADP), whose multiple low affinity DnaA recognition sites bind DnaA-ATP and DnaA-ADP similarly, was fully occupied and unwound by DnaA-ADP in vitro, and in vivo suppressed the lethality of DnaA mutants defective in ATP binding and ATP-specific oligomerization. However, despite their functional equivalency, orisomes assembled on oriCallADP were unable to trigger chromosome replication at the correct cell cycle time and displayed a hyper-initiation phenotype. Here we present a new perspective on DnaA-ATP, and suggest that in E. coli, DnaA-ATP is not required for mechanical functions, but rather is needed for site recognition and occupation, so that initiation timing is coupled to DnaA-ATP levels. We also discuss how other bacterial types may utilize DnaA-ATP and DnaA-ADP, and whether the high diversity of replication origins in the bacterial world reflects different regulatory strategies for how DnaA-ATP is used to control orisome assembly.